Friction behavior of a microstructured polymer surface inspired by snake skin - Baum, Martina J.; Heepe, Lars; Gorb, Stanislav N. (Beilstein Journal of Nanotechnology, 2014)
The aim of this study was to understand the influence of microstructures found on ventral scales of the biological model, Lampropeltis getula californiae, the California King Snake, on the friction behavior. For this purpose, we compared snake-inspired anisotropic microstructured surfaces to other microstructured surfaces with isotropic and anisotropic geometry. To exclude that the friction measurements were influenced by physico-chemical variations, all friction measurements were performed on the same epoxy polymer. For frictional measurements a microtribometer was used. Original data were processed by fast Fourier transformation (FFT) with a zero frequency related to the average friction and other peaks resulting from periodic stick-slip behavior. The data showed that the specific ventral surface ornamentation of snakes does not only reduce the frictional coefficient and generate anisotropic frictional properties, but also reduces stick-slip vibrations during sliding, which might be an adaptation to reduce wear. Based on this extensive comparative study of different microstructured polymer samples, it was experimentally demonstrated that the friction-induced stick-slip behavior does not solely depend on the frictional coefficient of the contact pair.
Keywords: fast Fourier transformation; friction; polymer; snake inspired; stick-slip

(untitled) - Renous, S.; Gasc, J. P.; Diop, A. (Fortschr. Zool., 1985)

(untitled) - Gray, J.; Lissmann, H. W. (J. Exp. Biol., 1950)

(untitled) - Marvi, H.; Hu, D. L. (J. R. Soc., Interface, 2012)

(untitled) - Leydig, F. (Archiv für mikroskopische Anatomie, 1873)

(untitled) - Hoge, A. R.; Santos, P. S. (Science, 1953)

(untitled) - Maderson, P. F. A. (Br. J. Herpetol., 1964)

(untitled) - Maderson, P. F. A. (Am. Zool., 1972)

(untitled) - Price, R. M. (Br. J. Herpetol., 1982)

(untitled) - Hazel, J.; Stone, M.; Grace, M. S.; Tsukruk, V. V. (J. Biomech., 1999)

(untitled) - Gower, D. J. (J. Morphol., 2003)

(untitled) - Berthé, R. A.; Westhoff, G.; Bleckmann, H.; Gorb, S. N. (J. Comp. Physiol., A, 2009)

(untitled) - Abdel-Aal, H. A.; Vargiolu, R.; Zahouani, H.; El Mansori, M. (Wear, 2012)

(untitled) - Schmidt, C.; Gorb, S. N. (Zoologica, 2012)

(untitled) - Klein, M.-C. G.; Gorb, S. N. (Zoologica)

(untitled) - Lancaster, J. K. (Brit. J. Appl. Phys., 1968)

(untitled) - Politi, Y.; Priewasser, M.; Pippel, E.; Zaslansky, P.; Hartmann, J.; Siegel, S.; Li, C.; Barth, F. G.; Fratzl, P. (Adv. Funct. Mater., 2012)

(untitled) - Benz, M. J.; Kovalev, A. E.; Gorb, S. N. (Proc. SPIE8339, 2012)

(untitled) - Spurr, A. R. (J. Ultrastruct. Res., 1969)

(untitled) - Li, K.; Ni, B. Y.; Li, J. C. M. (J. Mater. Res., 1996)

(untitled) - Jang, H.; Ko, K.; Kim, S. J.; Basch, R. H.; Fash, J. W. (Wear, 2004)

(untitled) - Nosonovsky, M.; Bhushan, B. (Mater. Sci. Eng., R, 2007)

Contact mechanics and friction – Physical principles and Applications - Popov, V. L. (Springer-Verlag, 2010)

Fundamentals of Tribology and Bridging the Gap Between the Macro- and Micro/Nanoscales - Bhushan, B. (Kluwer Academic Pub., 2001)

Sliding friction: physical principles and applications - Persson, B. N. J. (Springer-Verlag, 2000)

Biological micro- and nanotribology - Scherge, M.; Gorb, S. N. (Springer-Verlag, 2001)

(untitled) - Berman, A. D.; Ducker, W. A.; Israelachvili, J. N. (Langmuir, 1996)

(untitled) - Urbakh, M.; Klafter, J.; Gourdon, D.; Israelachvilli, J. (Nature, 2004)

(untitled) - Kinkaid, N. M.; O'Reilly, O. M.; Papadopoulos, P. (J. Sound Vibrat., 2003)

(untitled) - Cochard, A.; Bureau, L.; Baumberger, T. (J. Appl. Mech., 2003)

Friction and Wear of Materials - Rabinowicz, E. (John Wiley & Sons, 1965)

(untitled) - Varenberg, M.; Gorb, S. N. (Adv. Mater., 2009)

(untitled) - Murarash, B.; Itovich, Y.; Varenberg, M. (Soft Matter, 2011)

(untitled) - Yu, C.; Wang, J. Q. (Sci. Rep., 2012)

(untitled) - Klein, M.-C. G.; Gorb, S. N. (J. R. Soc. Interface, 2012)

(untitled) - Gray, J. (J. Exp. Biol., 1946)

Spezielle Zoologie-Teil 2: Wirbel- oder Schädeltiere - Westheide, W.; Rieger, R. (Springer-Verlag, 2004)

(untitled) - Gorb, S. N. (Microsc. Today, 2007)

(untitled) - Hertz, H. (Journal für die reine und angewandte Mathematik, 1881)

(untitled) - Peisker, H.; Gorb, S. N. (J. Exp. Biol., 2010)

(untitled) - Byerlee, J. D. (Tectonophysics, 1970)

(untitled) - Heslot, F.; Baumberger, T.; Perrin, B.; Caroli, B.; Caroli, C. (Phys. Rev. E, 1994)

(untitled) - Bhushan, B. (Wear, 2005)